2011
DOI: 10.2214/ajr.10.4881
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolization as Salvage Therapy for Hepatic Metastasis of Uveal Melanoma: A Single-Institution Experience

Abstract: Radioembolization is safe and effective salvage therapy for limited metastasis of uveal melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 30 publications
7
71
3
1
Order By: Relevance
“…In the first study of 11 patients investigating the use of 90 Y SIR-Spheres to treat uveal melanoma, a response rate of 100% and a 1-year survival rate of 80% were reported for the 10 subjects who could be contacted for follow-up, with 1 patient experiencing a complete response at 3 months as assessed by PET/CT [21]. Since the original investigation [21], more recent studies have reported median disease progression-free and overall survivals ranging from 4.7 to 5.9 and from 7 to 12.3 months, respectively, among patients with uveal melanoma liver metastases treated with 90 Y microsphere radioembolization [22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…In the first study of 11 patients investigating the use of 90 Y SIR-Spheres to treat uveal melanoma, a response rate of 100% and a 1-year survival rate of 80% were reported for the 10 subjects who could be contacted for follow-up, with 1 patient experiencing a complete response at 3 months as assessed by PET/CT [21]. Since the original investigation [21], more recent studies have reported median disease progression-free and overall survivals ranging from 4.7 to 5.9 and from 7 to 12.3 months, respectively, among patients with uveal melanoma liver metastases treated with 90 Y microsphere radioembolization [22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…For those with chemorefractory liver metastases, liverdirected therapy is a preferred approach to reduce tumor burden and prolong overall survival. Unfortunately, only a very small subset (~9%) of patients are eligible for resection (114,115). Treatment options for unresectable hepatic metastatic melanoma have historically been poor.…”
Section: Role Of Palliative Rt For Melanomasmentioning
confidence: 99%
“…Treatment options for unresectable hepatic metastatic melanoma have historically been poor. Recent studies utilizing Yttrium-90 ( 90 Y) radioembolization have led to encouraging results (114,(116)(117)(118). This is a special form of radiation that was initially established for the treatment of hepatocellular carcinoma and liver metastasis (119)(120)(121).…”
Section: Role Of Palliative Rt For Melanomasmentioning
confidence: 99%
“…Increasing numbers of patients with liver only recurrent breast cancer or (ocular) melanoma are reported [1][2][3]. The tumor specific pitfalls and recommendations regarding pre-SIRT imaging are discussed here under.…”
Section: Pre-treatment Tumor Extension Assessmentmentioning
confidence: 99%